2021
DOI: 10.3389/fncel.2021.664312
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Perforin-Mediated Neurotoxicity Attenuates Neurological Deficits After Ischemic Stroke

Abstract: Perforin-mediated cytotoxicity plays a crucial role in microbial defense, tumor surveillance, and primary autoimmune disorders. However, the contribution of the cytolytic protein perforin to ischemia-induced secondary tissue damage in the brain has not been fully investigated. Here, we examined the kinetics and subpopulations of perforin-positive cells and then evaluated the direct effects of perforin-mediated cytotoxicity on outcomes after ischemic stroke. Using flow cytometry, we showed that perforin+CD45+ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…These data suggest CD8 T cells act via the Prf1 pathway to impair retinal and BRB repair mechanisms. Recently, the Prf1 pathway has also been associated with different CNS diseases spanning from the eye to the brain, such as choroidal neovascularization in AMD patients, but also in mouse models of experimental stroke [ 107 ], TBI [ 33 ], Parkinson's [ 108 ], and Alzheimer’s diseases [ 109 ]. Relevant to our findings, Matsubara et al [ 110 ] demonstrated that retinal degeneration, either due to aging or pathological conditions associated with AMD, is worsened by an increased presence of Prf1 immunoreactive cells in the outer retina.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest CD8 T cells act via the Prf1 pathway to impair retinal and BRB repair mechanisms. Recently, the Prf1 pathway has also been associated with different CNS diseases spanning from the eye to the brain, such as choroidal neovascularization in AMD patients, but also in mouse models of experimental stroke [ 107 ], TBI [ 33 ], Parkinson's [ 108 ], and Alzheimer’s diseases [ 109 ]. Relevant to our findings, Matsubara et al [ 110 ] demonstrated that retinal degeneration, either due to aging or pathological conditions associated with AMD, is worsened by an increased presence of Prf1 immunoreactive cells in the outer retina.…”
Section: Discussionmentioning
confidence: 99%
“…Perforin-2/macrophage-expressed protein 1 is one of the oldest membrane attack complexes of complement [188]. In ischemic stroke the number of macrophages expressing perforin increase largely until day 3 after stroke, and then moderately decline [189].…”
Section: Brain Macrophages Responses To Strokementioning
confidence: 99%
“…Therefore, reduced adenosine triphosphate production (ATP) production and sodium–potassium pump malfunction lead to mitochondrial dysfunction and bioenergetic collapse ( Amantea and Bagetta, 2017 ). The pathological processes described above lead to the deterioration of membrane ion gradients, calcium influx, and increased release of amino acids, including toxic concentrations of the excitatory neurotransmitter glutamate and aspartate ( Globus et al, 1988 ; Pan et al, 2021 ). In the acute phase following ischemic injury, excessive release of glutamate, and dramatic dysfunction of glutamate transporters in astrocytes, accumulation of glutamate cause excitotoxicity-mediated neuronal apoptosis death ( Lai et al, 2014 ; Shen et al, 2022 ).…”
Section: Involvement Of Circadian In Neurotoxicity and Neuroprotectio...mentioning
confidence: 99%